Optical microscopy and autofluorescence recognition of toxoplasma gondii and cryptosporidium parvum oocysts (2017)
OocystsToxoplasma gondii and Cryptosporidium parvum were visualized using conventional optical microscopy (Olympus microscope CX31), allowing recognize their main morphological characteristics. In addition, its ability to autofluorescence when were exposed to certain range of ultraviolet light was confirmed. Cryptosporidium parvum presented autofluorescence under the FITC filter (excitation 450-490 nm and emission 515 nm) and Toxoplasma gondii under (excitation 330-380 nm and emission 397 nm) UV filter. The above was done to develop an autofluorescence experimental protocol for recognition of C. parvum and T. gondii oocysts in samples of raw cow’s milk.